Training system in team sports under modern conditions of sports reserve preparation - Guba, V.P.; Rodin, A.V.; Ananyin, A.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to generalise the current directions of the existing training system in team sports taking into account modern conditions of sports reserve preparation. Methods and structure of the study. To determine and substantiate the current directions for improving supplementary educational programmes in team sports under modern conditions of domestic sport development and sports reserve preparation, theoretical methods-actions (operations), empirical methods, logical methods, as well as systems methods were used. Results and conclusions. The approach proposed in the article determines a long-term strategy for the development of team sports that contributes to the successful resolution of effective sports reserve preparation tasks under conditions of international sanctions restricting the participation of domestic players in competitions. Regulation of the sports reserve preparation system indicates the expediency of revising the entire training system for athletes in team sports.